Conjugation with gold nanoparticles improves the stability of the KT2 peptide and maintains its anticancer properties. Issue 1 (20th December 2021) - Maraming, Pornsuda; Daduang, Jureerut; Kah, James Chen Yong
Abstract : One of the major weaknesses of therapeutic peptides is their sensitivity to degradation by proteolytic enzymes in vivo . Abstract : One of the major weaknesses of therapeutic peptides is their sensitivity to degradation by proteolytic enzymes in vivo . Gold nanoparticles (GNPs) are a good carrier for therapeutic peptides to improve their stability and cellular uptake in vitro and in vivo . We conjugated the anticancer KT2 peptide as an anticancer peptide model to PEGylated GNPs (GNPs-PEG) and investigated the peptide stability, cellular uptake and ability of the GNPs-KT2-PEG conjugates to induce MDA-MB-231 human breast cancer cell death. We found that 11 nm GNPs protected the conjugated KT2 peptide from trypsin proteolysis, keeping it stable up to 0.128% trypsin, which is higher than the serum trypsin concentration (range 0.0000285 ± 0.0000125%) reported by Lake-Bakaar, G. et al., 1979. GNPs significantly enhanced the cellular uptake of KT2 peptides after conjugation. Free KT2 peptides pretreated with trypsin were not able to kill MDA-MB-231 cells due to proteolysis, while GNPs-KT2-PEG was still able to exert effective cancer cell killing after trypsin treatment at levels comparable to GNPs-KT2-PEG without enzyme pretreatment. The outcome of this study highlights the utility of conjugated anticancer peptides on nanoparticles to improve peptide stability and retain anticancer ability.